Giardiasis and poor vitamin A status among aboriginal school children in rural Malaysia - Al-Mekhlafi, H.M.; Surin, J.; Sallam, A.A.; Abdullah, A.W.; Mahdy, M.A.K. (2010)
A cross-sectional study was carried out on 241 primary schoolchildren in Pahang, Malaysia to update their vitamin A status and to investigate the association of poor vitamin A status with their health and socioeconomic factors. All children were screened for intestinal parasitic infections. Blood samples were collected and vitamin A status was assessed. Socioeconomic data were collected by using pre-tested questionnaires. The results showed that 66 (27.4) children had low serum retinol levels (< 0.70 Î¼mol/L). Giardiasis and severe ascariasis were significantly associated with low serum retinol levels (P = 0.004 and P = 0.018, respectively). Logistic regression confirmed the significant association of giardiasis with low serum retinol (odds ratio = 2.7, 95 confidence interval = 1.3â5.5). In conclusion, vitamin A deficiency is still a public health problem in rural Malaysia. Vitamin A supplementation and treatment of intestinal parasitic infections should be distributed periodically to these children to improve their health and nutritional status.